2014
DOI: 10.1080/09500839.2014.955547
|View full text |Cite|
|
Sign up to set email alerts
|

Twinning stress prediction in bcc metals and alloys

Abstract: The development of a twin stress relationship for bcc metals and alloys in agreement with experiments has been both scientifically challenging and technologically vital. A modified approach to Peierls-Nabarro model is formulated that predicts the twinning stress in excellent agreement with experiments. We utilize the first principles energy calculations to extract the energy landscape associated with twinning and obtain the disregistry function to account for the interaction of multiple dislocations comprising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 63 publications
3
16
0
Order By: Relevance
“…The potential was already used for the simulation of tensile and compressive deformation of α‐Fe . Previous simulations also showed that twinning is the dominant deformation mode for α‐Fe nanowires under tension, which is consistent with our simulations where twinning always nucleates from the tensile region of the sample under bending. The potential correctly predicted the sixfold core structure of screw dislocation as confirmed by DFT calculations .…”
Section: Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…The potential was already used for the simulation of tensile and compressive deformation of α‐Fe . Previous simulations also showed that twinning is the dominant deformation mode for α‐Fe nanowires under tension, which is consistent with our simulations where twinning always nucleates from the tensile region of the sample under bending. The potential correctly predicted the sixfold core structure of screw dislocation as confirmed by DFT calculations .…”
Section: Methodssupporting
confidence: 90%
“…The generalized stacking fault energy, interstitial and vacancy formation energy, thermal expansion, and dislocation properties predicted by the potential are in good agreement with density functional theory (DFT) calculations . The potential was already used for the simulation of tensile and compressive deformation of α‐Fe . Previous simulations also showed that twinning is the dominant deformation mode for α‐Fe nanowires under tension, which is consistent with our simulations where twinning always nucleates from the tensile region of the sample under bending.…”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…Based on this slip system, the Burgers vector (b) for B19 Ti-6.25Zr-25Nb lattice is equal to 3.24 Å , for example. The GSFE is obtained by shearing one half (001) plane of the crystal with respect to another half by continuous rigid displacements of u x = nb along [100] direction, where b is the magnitude of the Burgers vector and n is a parameter ranging from 0 to 1 [18][19][20]. Similarly, Fig.…”
Section: Slip and Gsfe Curves In B19 Ti-based Alloysmentioning
confidence: 99%
“…This process requires overcoming the twinning energy barrier represented by the generalized planar fault energy (GPFE). The GPFE is the energy per unit area required to nucleate a twin [13][14][15] and will be discussed later. Upon subsequent heating above the austenite finish (A f ) temperature, the detwinned martensite reverts back to austenite, giving rise to shape memory effect.…”
Section: Introductionmentioning
confidence: 99%